Doing business with Japan : successful strategies for intercultural communication - Nishiyama, Kazuo (Latitude 20 Bks., 2000)
In Japan, evidence of the country's Westernization abounds, yet despite appearances, it has remained "uniquely" Japanese. For this reason, the uninformed Westerner doing business there will find it difficult and even frustrating to work with Japanese unless he or she gains a good understanding of Japan and its people. The author draws on his extensive bilingual and bicultural experience to provide readers with an insightful look at many key aspects of doing business with Japan, ranging from initiating and maintaining business contacts, effective interpersonal communication, decision-making styles, negotiation tactics, presentational speaking, working of Japanese multinational companies, and living and working in Japan. Businesspeople, academics, non-academics, students, and others who are interested in learning how to communicate effectively and successfully with Japanese in international business contexts will benefit from the author's sound recommendations and advice